2014
DOI: 10.3892/mmr.2014.2207
|View full text |Cite
|
Sign up to set email alerts
|

Anti-fibrotic effects of specific-siRNA targeting of the receptor for advanced glycation end products in a rat model of experimental hepatic fibrosis

Abstract: Since the receptor for advanced glycation end products (RAGE)-ligand axis has been demonstrated to be important in fibrogenesis, rat models may be used to assess whether specific small interfering RNAs (siRNAs) that target RAGE are able to reduce the progression of hepatic fibrosis. However, the effect of RAGE-targeted siRNA on established hepatic fibrosis remains to be elucidated. In the present study, RAGE-specific siRNA expression vectors were constructed prior to the animal experiment. Sprague-Dawley rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…This is possibly achieved by acting upon many possible sites in the proposed pathway; first by preventing oxidative stress, second by inhibiting the synthesis of proinflammatory cytokines (TGF-b) and thirdly by combating extracellular matrix accumulation via upregulating TIMPs. Previous results have reported the ability of AGEs to induce oxidative stress as well as proinflammatory cytokines [34] and the ability of aminoguanidine to inhibit oxidative stress [35] and to decrease lung fibrosis [36].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is possibly achieved by acting upon many possible sites in the proposed pathway; first by preventing oxidative stress, second by inhibiting the synthesis of proinflammatory cytokines (TGF-b) and thirdly by combating extracellular matrix accumulation via upregulating TIMPs. Previous results have reported the ability of AGEs to induce oxidative stress as well as proinflammatory cytokines [34] and the ability of aminoguanidine to inhibit oxidative stress [35] and to decrease lung fibrosis [36].…”
Section: Discussionmentioning
confidence: 98%
“…The expression levels of RAGE together with IL-6, TNF-α, TGF-β1, connective tissue growth factor, laminin, hyaluronic acid and N-terminal procollagen III in the treated primary HSCs were significantly downregulated compared with those in the untreated. Thus, it can be deduced that RAGE-specific siRNAs inhibited the expression of RAGE in primary rat HSCs and inhibited the development of HF [36].…”
Section: Discussionmentioning
confidence: 99%
“…7B). Finally, since several studies report that COMP is able to signal via Cd47 [46], Cd36 [47], Rage [48] and α v β 3 -Integrin [49] we analyzed their mRNA expression. Cd36 mRNA was up-regulated upon TAA-or CCl 4 -induced liver fibrosis in WT but not in Comp −/− mice (Fig.…”
Section: Rcomp Up-regulates Collagen-i Expression In Hscs Via Cd36 Rementioning
confidence: 99%
“…(Zhang et al 2007a). Improved fibrosis and steatosis (Kitamura et al 2007) (d) Novel molecular target RAGE siRNA injected to CCl4-treated rats (Cai et al 2014) Inhibited RAGE expression, improved liver function, reduced inflammatory cytokines, and improved fibrotic stage Inhibited TG activation by propolis in TAA-treated rats (Chen et al 2008) Prevented the development of TAA-induced liver cirrhosis (e) Nanotechnology applications in liver fibrosis MSP-HSA coupled to liposomes and HVJ in CCl4-treated mice (Adrian et al 2007) M6P-HSA-HVJ liposomes accumulate in HSCs Delivered rosiglitazone by MSP-HAS liposomes in CCl4-treated rats (Patel et al 2012) Enhanced rosiglitazone liver uptake and disappeared from systemic circulation. Improved histopathological morphology, biochemical markers level, and decreased fibrosis grade RGD-labeled liposomes encapsulated IFNα-1b in BDL-treated rats (Du et al 2007) Accumulation of cRGD peptide-labeled liposomes in HSCs, reduced extent of liver fibrosis Vitamin A-coupled liposomes containing gp46 siRNA in DMN-treated rats (Sato et al 2008) Suppressed collagen secretion and fibrosis…”
Section: Other Relevant Molecular Targets and Other Possible Anti-fibmentioning
confidence: 99%
“…Novel molecular targets: In vitro studies indicated that serum high mobility group box 1 (HMGB1) levels were positively correlated with TGF-β production and collagen deposition during fibrogenesis through receptor of advanced glycation end products (RAGE) pathway activation. CCl4-treated SD rats administered RAGE-specific siRNA twice weekly via tail vein injection for up to 6 weeks displayed significantly decreased levels of serum inflammatory cytokines, NFκB, procollagen III, and hepatic fibrosis, suggesting that HMGB1/RAGE may be a novel target to prevent liver fibrosis (Cai et al 2014). Tissue transglutaminase (tTG) was found to co-localize with collagen fibers to contribute to the development of liver fibrosis.…”
Section: Tgf-β Collagen and Attenuated Fibrosismentioning
confidence: 99%